Bidirectional Mechanical Response Between Cells and Their Microenvironment - Mierke, Claudia Tanja (Frontiers in Physics, 2021)
Cell migration and invasion play a role in many physiological and pathological processes and are therefore subject of intensive research efforts. Despite of the intensively investigated biochemical processes associated with the migration and invasion of cells, such as cancer cells, the contribution of mechanobiological processes to the migratory capacity of cells as well as the role of physical polymeric phase transitions is not yet clearly understood. Unfortunately, these experiments are not very informative because they completely disregard the influence of the three-dimensional cell environment. Despite this data situation, it was possible to adequately demonstrate that there exists a direct mechanical interplay between cells and their microenvironment in both directions, where both elements can be mechanically altered by one another. In line with these results, it has turned out that the mechanobiological molecular processes through which cells interact with each other and additionally sense their nearby microenvironment have an impact on cellular functions such as cellular motility. The mechanotransduction processes have become the major focus of biophysical research and thereby, diverse biophysical approaches have been developed and improved to analyze the mechanical properties of individual cells and extracellular matrix environments. Both, the cell mechanics and matrix environment mechanics regulate the cell migration types in confined microenvironments and hence it seems to be suitable to identify and subsequently present a common bidirectional interplay between cells and their matrix environment. Moreover, hallmarks of the mechanophenotype of invasive cells and extracellular matrices can be defined. This review will point out how on the one hand the intracellular cytoskeletal architecture and on the other hand the matrix architecture contribute to cellular stiffness or contractility and thereby determines the migratory phenotype and subsequently the emergence of a distinct migration mode. Finally, in this review it is discussed whether universal hallmarks of the migratory phenotype can be defined.